Pancasila Philosophy as the Basis of Education and National Character - Utaminingsih, Esty Setyo; Ihsandi, Aldi; Mutiarawati, Intan Shih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Pancasila philosophy is a guideline for life that underlies all aspects of national life, including in the line of education in Indonesia. This study aims to examine more about Pancasila philosophy as the basis of education and national character. The method in this study uses the method of literature review. The results of the literature review show that the philosophy of Pancasila plays a vital role in formulating the curriculum to strengthen the values of national character that is tolerant, solidarity, cares for social justice, and has good morals and can prevent moral degradation in massive technological development. The philosophy of Pancasila plays an essential role in education and cultivating Pancasila values to prevent moral degradation.